Persepsi Ibu Terhadap Perkembangan Sosial Emosional Anak Usia Dini Di Kelurahan Kayu Putih Kota Kupang - Tuke, Aplonia Marteda (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2025)
The socio-emotional development of early childhood plays an important role in shaping children’s character and social skills. This study aims to describe mothers’ perceptions of the socio-emotional development of early childhood in Kelurahan Kayu Putih, Kota Kupang. Participants were selected using purposive sampling. Through a descriptive qualitative approach, data were collected via interviews with six mothers who have children aged 3–6 years and were analyzed using thematic analysis techniques. The results showed that mothers in Kelurahan Kayu Putih understand socio-emotional development as a process in which children are able to interact and adapt to their environment, express and communicate their feelings, and cope with minor problems during play. The parenting strategies applied tended to use a democratic parenting style, carried out through simple activities in daily routines such as playing with children, storytelling, or doing household chores together. In practice, mothers faced challenges including limited time, the influence of electronic media, as well as economic and emotional pressures. Nevertheless, mothers continue to hope that their children will grow into empathetic and emotionally independent individuals. These findings indicate that mothers’ perceptions of socio-emotional development are formed not only from theoretical knowledge but also from direct interaction and everyday habits at home. Therefore, it is important for educational institutions and related stakeholders to appreciate and strengthen the positive perceptions that mothers already have through counseling or discussions related to parenting and early childhood development. In this way, mothers’ understanding can continue to develop and serve as a strong foundation for their children’s growth.